Emotion regulation and sport confidence among student athletes: The moderating role of gender - Maulidiyah, Elok Faiqoh; Jannah, Miftakhul (UIR Press, 2026)
Background: Academic pressure and competitive demands can cause psychological stress in student-athletes who are still in the stage of social-emotional development. This condition can affect their ability to regulate emotions and maintain sport confidence during competition. However, empirical evidence examining gender as a moderating factor in the relationship between emotion regulation and sport confidence among student-athletes remains limited. Objectives: The research goal is to examine the effect of emotion regulation on sport confidence, moderated by gender role among student athletes. Methods: A cross-sectional quantitative design was employed involving 113 student athletes. Data analysis used the Moderation Regression Analysis (MRA) technique with gender as a moderating variable. Emotion regulation was measured using instruments from ERQ–Short Form and sport confidence from TRSCI. Results: The results indicated that emotion regulation ability is a significant predictor of sport confidence (p < 0.001); the better student athletes can regulate their emotions, the higher their level of sport confidence. Additionally, gender was found to significantly moderate this relationship (p = 0.028). The combined effects of emotion regulation and gender can explain 20.2% of the variation in sports confidence (R² = 0.202). Conclusion: This study concludes that emotional regulation ability is an important factor in sport confidence among student athletes, with differing effects based on gender. These findings have practical implications for sports mental coaches in designing gender-based emotional regulation training to improve student-athlete sport confidence, such as mindfulness training, and open opportunities for further research with a longitudinal approach and other psychological variables.